Aspectos da socialidade da existência na fenomenologia hemenêutica de Ser e Tempo - Tonin, Jean (2017)
The present research aims to explain the fundamental aspects of the sociality of human existence, according to Heidegger's exposition of Being and Time. In his work, starting from the questioning of the sense of being in general, the philosopher produces an analysis of human existence, which is systematically understood by the term being-there (Dasein). In such analysis, the social character of existence is ontologically explained by the characterization of the fundamental structure of existence, namely: being-with (Mitsein). In an attempt to expose the determining characters of the being-with structure and to point out the aspects that characterize the relationship between being-there and its similar, our research is divided into three moments. Firstly, we will reconstruct the analysis of everyday being-there, which requires the exposure of the introductory aspects of the work and the characterization of the constitutive moments of the most fundamental structure of existence, there called being-in-the-world. Further, we are able to see that on the positive exposure of the way of being the one (das Man), which characterizes the way by which the everyday being-there is sustained, it is verified a primacy of impropriety in existence, prompt and more often submerged in normative patterns of behavior regulated publicly. This way of being is called the one sociality. In the second moment, based on the description of concepts of anguish, guilt , death and consciousness, the characters of the existential modification are exposed, in which the being-there severs from the daily way of being and presumes to be a fundament in the uniqueness of its existence. However, we will see that this uniqueness does not exclude all rules and patterns, but rather departs from it, and existence relates itself consciously and in its own way to patterns, responsively projecting into existential possibilities, constituted inter-subjectively. In such finding, the perspective of the second person is visible, in which it is found that the being-there is in a relationship of mutual responsibility towards the other. Finally, based on the exposition of the temporality and historicity of existence, we will explain how the resolute of happening (Geschehen) in the being-there occurs in the "between" of the existential ends denominated birth and death.